Associations among multidomain lifestyles, chronic diseases, and dementia in older adults: a cross-sectional analysis of a cohort study - Zhang, Jing-jing; Wu, Zhao-xia; Tan, Wei; Liu, Dan; Cheng, Gui-rong; Xu, Lang; Hu, Fei-fei; Zeng, Yan (Frontiers in Aging Neuroscience, 2023)
Background Unhealthy lifestyles and chronic diseases are commonly seen and treatable factors in older adults and are both associated with dementia. However, the synergistic effect of the interaction of lifestyles and chronic diseases on dementia is unknown. Methods We determined independent associations of multidomain lifestyles and chronic diseases (cerebrovascular disease, diabetes, and hypertension) with dementia and examined their synergistic impact on dementia among older adults. The data were drawn from the Hubei Memory and Aging Cohort Study. We created a summary score of six factors for multidomain lifestyles. Dementia was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders IV. Logistic regression and multiple correspondence analyses were used to explore the relationships among multidomain lifestyles, chronic diseases, and dementia. A sensitivity analysis was performed to minimize the interference of reverse causality and potential confounders. Results Independent associations with dementia were found in unhealthy (OR = 1.90, 95% CI: 1.38–2.61) and intermediate healthy lifestyles (OR, 3.29, 2.32–4.68), hypertension (OR, 1.21, 1.01–1.46), diabetes (OR, 1.30, 1.04–1.63), and cerebrovascular disease (OR, 1.39, 1.12–1.72). Interactions of diabetes (p = 0.004), hypertension (p = 0.004), and lifestyles were significant, suggesting a combined impact on dementia. Sensitivity analysis supported the strong association among multidomain lifestyles, chronic diseases, and dementia prevalence. Conclusion An unhealthy lifestyle was associated with a higher prevalence of dementia, regardless of whether the participants had chronic diseases; however, this association was stronger in individuals with chronic diseases. Multidomain lifestyles and chronic diseases may have an enhanced impact on dementia.